2022
DOI: 10.1002/adsc.202200209
|View full text |Cite
|
Sign up to set email alerts
|

Well‐Defined Ni−SNS Complex Catalysed Borrowing Hydrogenative α‐Alkylation of Ketones and Dehydrogenative Synthesis of Quinolines

Abstract: The "borrowing hydrogen" (BH) method for C-alkylation reactions using alcohol as alkylating agents is an important synthetic transformation. In this respect, designing cheap and bench stable earth abundant metal catalyst for borrowing hydrogen transformation is a key challenge to be witnessed. Herein we have presented a synthesis of non-phosphine, easily accessible and bench stable SNSÀ Ni complexes. The Ni-catalyst was successfully applied for the C-alkylation of ketone enolates to α-alkylated ketones. Primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…69 It is worth mentioning that, during the preparation of this manuscript, Srimani et al reported Ni-SNS complex catalyzed borrowing the hydrogenative α-alkylation of ketones and the dehydrogenative synthesis of quinolones. 92,93 Very interestingly, heteroatom containing fused-heterocyclic compounds have acquired huge demand due to their active and abundant presence in pharmaceutically/ biologically important compounds such as DNA cytosine deaminases APOBEC3G inhibitors (B), such as Donepezil drug (A), inhibitor of NAD-hydrolyzing enzyme CD38 (C), Clioquinol (antifungal) (E), Robustine (anticancer) (F), and ligand against Alzheimer's disease (D) 22 (S3, Figure S1). In this context, herein we disclose the efficient utility of biogenically synthesized single phase δ-MnO 2 NPs for catalytic dehydrogenation of aryl alcohol to form a carbonyl compound.…”
Section: Applications Of δ-Mno 2 Nps For Organic Transformationsmentioning
confidence: 99%
See 1 more Smart Citation
“…69 It is worth mentioning that, during the preparation of this manuscript, Srimani et al reported Ni-SNS complex catalyzed borrowing the hydrogenative α-alkylation of ketones and the dehydrogenative synthesis of quinolones. 92,93 Very interestingly, heteroatom containing fused-heterocyclic compounds have acquired huge demand due to their active and abundant presence in pharmaceutically/ biologically important compounds such as DNA cytosine deaminases APOBEC3G inhibitors (B), such as Donepezil drug (A), inhibitor of NAD-hydrolyzing enzyme CD38 (C), Clioquinol (antifungal) (E), Robustine (anticancer) (F), and ligand against Alzheimer's disease (D) 22 (S3, Figure S1). In this context, herein we disclose the efficient utility of biogenically synthesized single phase δ-MnO 2 NPs for catalytic dehydrogenation of aryl alcohol to form a carbonyl compound.…”
Section: Applications Of δ-Mno 2 Nps For Organic Transformationsmentioning
confidence: 99%
“…[101][102][103] The plausible mechanism is depicted for the δ-MnO 2 NPs catalyzed alkylation and the cyclization reaction with the help of literature presidents and control experiments (Scheme 5). [55][56][57][58][59][60][61][62][63][64][65][66][67][68][92][93][94][95] The biogenically synthesized δ-MnO 2 NPs facilitate the dehydrogenation of benzyl alcohol via HA strategy to form a benzaldehyde, which subsequently gets coupled with the enolate of acetophenone, leading to the aldol product 3 0 upon elimination of water. Further, hydrogen shuttling by catalyst helps to deliver alkylation product 3 completing the ADC reaction with the elimination of catalyst for the next cycle.…”
Section: Applications Of δ-Mno 2 Nps For Organic Transformationsmentioning
confidence: 99%
“…In this regard, the concept of ''Hydrogen Auto-transfer (HA)'' or ''borrowing hydrogen (BH)'' has been a significant achievement in the scientific community's efforts toward developing more sustainable and environmentally benign chemical processes. 5 The HA or BH strategy involves the transfer of hydrogen atoms from a hydrogen donor to an acceptor. The method has effectively been applied to chemical reactions including reduction, oxidation, and cross-coupling reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The chemistry of three-membered heterocycles has played a prevalent role in organic synthesis, where the innate ring strain is harnessed to unearth new synthetic transformations . In this regard, the regioselective ring-opening of epoxides synthesizing β–functionalized secondary alcohols is an intriguing transformation . Secondary alcohols are one of the essential building blocks in organic synthesis and are present in various pharmaceuticals, agrochemicals, and fragrances .…”
Section: Introductionmentioning
confidence: 99%